Spare parts optimization for maintenance of electronic module constructed devices - Dušan Korolija (Vojnotehnički Glasnik, 1996)
The paper presents spare parts model supply for one type of electronic module constructed devices, in a multilevel maintenance system. The procedure of spare parts optimization for maintenance of such devices is explained and an example of spare parts optimisation of a hypothetic electronic device is presented. The example includes the spare parts saving analysis in the dependence on logistics parameters.